A small-molecule with a large two-photon absorption cross-section serves as a membrane-permeable ribonucleic acid (RNA) probe for live cell imaging. (3rd August 2018) - Feng, Ruiqing; Li, Longlong; Li, Bing; Li, Jinhui; Peng, Dan; Yu, Yitao; Mu, Qiuhong; Zhao, Ning; Yu, Xiaoqiang; Wang, Zhenhua
Abstract : DMI could light up the RNA of the nucleus and the cytoplasm in living systems, which not only exhibits larger two-photon absorption cross-sections (981 GM), but also displays high-permeability to plasma membranes of vigorous cells. Abstract : We have synthesized a two-photon organic small-molecule probe (DMI ), which has a considerable two-photon absorption cross section ( δ ) value and selectively stained endogenous RNA in the nucleolus and the cytoplasm of living cells with outstanding membrane permeability. The titrations, fluorescence imaging and RNase digest test indicate markedly higher affinity for endogenous RNA. The double assay ofDMI and SYTOX Blue nucleic acid stain (S-11348) showed that the probe possesses excellent membrane permeability to living cells, and a co-staining experiment with the classic DNA-staining dye DAPI indicated that it has excellent counterstain compatibility. Moreover, DMI exhibited good photostability when continuously illuminated by constant femtosecond pulses. These results demonstrate thatDMI is an attractive two-photon fluorescent probe for visualizing RNA in living cells.